DESIGN AND DISCOURSE OF MODERN STANDARD ARABIC E-TEXTBOOK - Thohir, Muhammad; Kurjum, Mohammad; Muhid, Abdul (LITERA, 2020)
An E-textbook of Modern Standard Arabic (MSA) is an important device that supports the on-line practical aspects of the teaching Arabic as a foreign language (TAFL). The present study was aimed at describing the characteristics of the design and discourse of the Schulz’s E-textbooks of MSA. The study focused on Schulz MSA E-Textbook as an instructional material package of standard Arabic of the intermediate levels (B1 and B2 levels). The study used the qualitative research approach with the discourse-analysis method of data analyses.The results showed the following findings. The design of the E-package is web-based with multimedia as resources. The content prioritizes on grammar material in each initial lesson unit of the textbook. Although standard modern Arabic is used as the language variant for the language skills, colloquial language variants are given sufficient attention that can be accessed only in the E-edition version of the package. In terms of the contents of the discourse, a wide selection of texts are used with varied themes in the field of education, social affairs, economy, culture, politics, religion, environment, and technology. Citations embedded in header texts do not always match the contents of the discourse. The religious discourse pieces in the materials seem to be positioned more as socio-cultural facts rather than as theological facts. Keywords: E-textbook, Modern Standard Arabic, discourse, learning material DESAIN DAN WACANA BUKU PELAJARAN BAHASA ARAB BAKU Abstrak Buku ajar elektronik bahasa Arab standar merupakan perangkat penting yang mendukung aspek-aspek praktis online pada pembelajaran bahasa Arab sebagai bahasa asing (PBABA). Penelitian ini bertujuan untuk menggambarkan karakteristik desain dan muatan wacana buku ajar elektronik bahasa Arab Standar. Kajian difokuskan pada e-text karya Eckehard Schulz yang banyak digunakan di Indonesia dan dibatasi pada tingkat menengah (tingkat B1-B2). Penelitian menggunakan pendekatan penelitian deskriptif kualitatif dengan analisis wacana. Hasil penelitian menunjukkan temuan berikut. Desain e-textbook MSA Schulz berkarakter web based dengan multimedia sebagai resources. Kontennya memprioritaskan materi tata bahasa di setiap awal pelajaran. Meskipun keterampilan berbahasa Arab ditekankan pada penggunaan variasi standar atau modern language, variasi colloquial language mendapat perhatian cukup memadai yang hanya dapat diakses dalam versi e-edition. Dari segi muatan wacana, ia menghadirkan banyak muatan seperti pendidikan, sosial, ekonomi, budaya, politik, agama, lingkungan, dan teknologi. Kutipan yang disematkan di setiap header halaman tidak selalu cocok dengan isi wacana. Yang menarik, wacana agama di dalamnya terlihat lebih diposisikan sebagai fakta sosial-budaya daripada fakta teologis. Kata kunci: buku elektronik, bahasa Arab standar, wacana, kegiatan pembelajaran